PENGARUH INVESTASI PMA DAN PMDN TERHADAP PERTUMBUHAN EKONOMI KOTA PEKANBARU - Syakirah Athiyyah Fitri; Wellyn Cesharina Meylan; B. Isyandi; Ufira Isbah; Dahlan Tampubolon (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to analyze the influence of Foreign Direct Investment (FDI) and Domestic Direct Investment (PMDN) on the economic growth of Pekanbaru City from 2016 to 2025. Fluctuations in the realization of FDI and PMDN, which do not always align with economic growth, are the background to this research. The quantitative approach used was multiple linear regression, using secondary time series data processed using EViews 12 software. The results indicate that FDI partially has no significant effect on economic growth, while PMDN has a positive and significant effect. Meanwhile, both FDI and PMDN simultaneously have a significant effect on economic growth. The Adjusted R-Squared value of 0.804 indicates that 80.43% of the variation in economic growth can be explained by the two independent variables in the research model. This finding indicates that domestic investment plays a more dominant role than foreign investment in driving Pekanbaru City's economic growth.